Not All Fibers Are Born Equal; Variable Response to Dietary Fiber Subtypes in IBD - Armstrong, Heather; Mander, Inderdeep; Zhang, Zhengxiao; Armstrong, David; Wine, Eytan (Frontiers in Pediatrics, 2021)
Diet provides a safe and attractive alternative to available treatment options in a variety of diseases; however, research has only just begun to elucidate the role of diet in chronic diseases, such as the inflammatory bowel diseases (IBD). The chronic and highly debilitating IBDs, Crohn disease and ulcerative colitis, are hallmarked by intestinal inflammation, immune dysregulation, and dysbiosis; and evidence supports a role for genetics, microbiota, and the environment, including diet, in disease pathogenesis. This is true especially in children with IBD, where diet-based treatments have shown excellent results. One interesting group of dietary factors that readily links microbiota to gut health is dietary fibres. Fibres are not digested by human cells, but rather fermented by the gut microbes within the bowel. Evidence has been mounting over the last decade in support of the importance of dietary fibres in the maintenance of gut health and in IBD; however, more recent studies highlight the complexity of this interaction and importance of understanding the role of each individual dietary fibre subtype, especially during disease. There are roughly ten subtypes of dietary fibres described to date, categorized as soluble or insoluble, with varying chemical structures, and large differences in their fermentation profiles. Many studies to date have described the benefits of the byproducts of fermentation in healthy individuals and the potential health benefits in select disease models. However, there remains a void in our understanding of how each of these individual fibres affect human health in dysbiotic settings where appropriate fermentation may not be achieved. This review highlights the possibilities for better defining the role of individual dietary fibres for use in regulating inflammation in IBD.